Exploring English Department Students' Perceptions of Character AI in Enhancing Speaking Fluency: A Case Study - Indaha Nawaya Kafabina; Hendi Pratama (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
In the era of rapid technological advancement, English-speaking fluency has become an essential skill for EFL learners. However, many students still face difficulties in developing speaking fluency due to limited opportunities for practice and psychological barriers such as anxiety and lack of confidence. This study explores English Department students’ perceptions of the use of Character AI in enhancing speaking fluency. This research employed a qualitative case study design involving ten students from Universitas Negeri Semarang. Data were collected through classroom observations and semi-structured interviews and were analyzed using thematic analysis. The findings reveal that Character AI positively contributes to students’ speaking development by improving fluency, enriching vocabulary, and increasing confidence through a low-anxiety learning environment. In addition, the AI functions as a scaffolding partner that supports students in maintaining conversations and provides flexible opportunities for independent practice. However, several challenges were identified, including technical issues, limited features, occasional inaccuracies, and a lack of emotional interaction. Overall, Character AI is considered a useful supplementary tool for improving speaking fluency. These findings suggest that Character AI can serve as an effective supplementary tool in EFL speaking instruction when integrated with human interaction.